2023
DOI: 10.3389/fpls.2023.1122397
|View full text |Cite
|
Sign up to set email alerts
|

Fruit growth and development in apple: a molecular, genomics and epigenetics perspective

Abstract: Fruit growth and development are physiological processes controlled by several internal and external factors. This complex regulatory mechanism comprises a series of events occurring in a chronological order over a growing season. Understanding the underlying mechanism of fruit development events, however, requires consideration of the events occurring prior to fruit development such as flowering, pollination, fertilization, and fruit set. Such events are interrelated and occur in a sequential order. Recent ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 165 publications
0
3
0
Order By: Relevance
“…Cucurbitaceae is the second largest family bearing diverse groups of plant with broad range of fruit characteristic (Shaina and Suhara Beevy, 2012;Ma et al, 2020). Studies related to fruit development and variations in fruit sizes are also reported in other plants like Arabidopsis, tomato, pear, pumpkin, cucumber, bottle gourd, apple, Apricot, sweet cherry among many others (Jiang et al, 2015;Xanthopoulou et al, 2017;Di Marzo et al, 2020;Yuste-Lisbona et al, 2020;Zhang et al, 2020;Kuhn et al, 2021;Liu et al, 2023;Wang et al, 2022;Jahed and Hirst, 2023). RNA-Seq analyses have become the most popular method to identify the key genes regulating fruit morphology in several cucurbit vegetables (Zhang et al, 2016;Ma et al, 2020;Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cucurbitaceae is the second largest family bearing diverse groups of plant with broad range of fruit characteristic (Shaina and Suhara Beevy, 2012;Ma et al, 2020). Studies related to fruit development and variations in fruit sizes are also reported in other plants like Arabidopsis, tomato, pear, pumpkin, cucumber, bottle gourd, apple, Apricot, sweet cherry among many others (Jiang et al, 2015;Xanthopoulou et al, 2017;Di Marzo et al, 2020;Yuste-Lisbona et al, 2020;Zhang et al, 2020;Kuhn et al, 2021;Liu et al, 2023;Wang et al, 2022;Jahed and Hirst, 2023). RNA-Seq analyses have become the most popular method to identify the key genes regulating fruit morphology in several cucurbit vegetables (Zhang et al, 2016;Ma et al, 2020;Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many external and internal factors influence fruit size including genetics, environment, cultivation practices etc. and have been studied in various reports ( Huang et al., 2023 ; Jahed and Hirst, 2023 ). Apart from these, molecular mechanisms such as cell division, cell expansion, and endoreduplication, play a vital role in determining fruit size and shape ( Chevalier et al., 2014 ; Okello et al., 2015 ; Mauxion et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation